Regnase-1-mediated post-transcriptional regulation is essential for hematopoietic stem and progenitor cell homeostasis - Hiroyasu Kidoya (Nature Portfolio, 2019)
Regnase-1 is known to mediate post-trasncriptional regulatory activity through degradation of target mRNAs. Here, the authors show that Regnase-1 regulates self-renewal of haematopoietic stem and progenitor cells through modulation of the stability of Gata2 and Tal1 mRNA.